Antimicrobial resistance of Pseudomonas aeruginosa: navigating clinical impacts, current resistance trends, and innovations in breaking therapies - Elfadadny, Ahmed; Ragab, Rokaia F.; AlHarbi, Maha; Badshah, Farhad; Ibáñez-Arancibia, Eliana; Farag, Ahmed; Hendawy, Amin Omar; De los Ríos-Escalante, Patricio R.; Aboubakr, Mohamed; Zakai, Shadi A.; Nageeb, Wedad M. (Frontiers in Microbiology, 2024)
Pseudomonas aeruginosa, a gGram-negative bacteriabacterium, is recognized for its adaptability and opportunistic nature. It poses a substantial challenge in clinical settings due to its intricate complicated antibiotic resistance mechanisms, biofilm formation, and capacity for persistent infections in both animal and human hosts. Our recent investigationsRecent studies revealed the a potential zoonotic transmission of P. aeruginosa between canine animals, the environment, and human populations which highlights awareness of this microbe, evidenced by genotyping studies of strains isolated from dogs. Implementation of the One Health approach, which underscores the connection between human, animal, and environmental health, we aim to offer a comprehensive perspective on the current landscape of P. aeruginosa management. This review delves intopresents innovative strategies designed to counteract P. aeruginosa infections. Traditional antibiotics, while effective in many cases, are increasingly compromised by the development of multidrug-resistant strains. Non-antibiotic avenues, such as quorum sensing inhibition, phage therapy, and nanoparticlebased treatments, are emerging as promising alternatives. However, their clinical application encounters obstacles like cost, side effects, and safety concerns. Effectively addressing P. aeruginosa infections necessitates persistent research efforts, advancements in clinical development, and a comprehension of host-pathogen interactions to deal with this resilient pathogen.